Determinansi Kepuasan Pasien Rawat Inap: Peran Dominan Kualitas Layanan Dokter dan Kompetensi Petugas - Andrew Santosa; Ahdun Trigono; Dicky Yulius Pangkey; Agustiawan Imron (Yayasan Literasi Sains Indonesia, 2026)
This study aimed to analyze the effect of service quality on inpatient satisfaction in a hospital setting. Service quality was assessed through several key dimensions, including fulfillment of patient needs, staff competence, physician service quality, and admission staff services. A quantitative observational analytic design was applied, and data were collected using structured questionnaires. Statistical analyses were performed using t-tests, chi-square tests, and linear regression to identify the most dominant influencing factor. The results demonstrated that all variables significantly affected patient satisfaction (p < 0.05). Physician services were identified as the most dominant factor in improving patient satisfaction (β = 0.379; p = 0.000). Fulfillment of patient needs, professional competence of staff, and efficient and friendly administrative services also played important roles in shaping positive perceptions of healthcare quality. The better the service quality provided, the higher the level of patient satisfaction during hospitalization. These findings emphasize the importance of continuous and comprehensive quality improvement to enhance patient trust and loyalty toward healthcare institutions.